THE INFLUENCE OF THE SPECIFICITY OF MOTORTANSPORT BRANCH ON INCOME AND EXPENSE CALCULATION - H. Mammadov; Z. Chebotareva (Вестник университета)
The specific features of taking account stock of motortransport enterprises are stated in this article. The main details concerning transport branch, types of income and expense rising at work of motortransport system are completely studied.